Diagnosis, natural history, and management in vascular Ehlers–Danlos syndrome. Issue 1 (March 2017) - Byers, Peter H.; Belmont, John; Black, James; De Backer, Julie; Frank, Michael; Jeunemaitre, Xavier; Johnson, Diana; Pepin, Melanie; Robert, Leema; Sanders, Lynn; Wheeldon, Nigel
Abstract : Vascular Ehlers Danlos syndrome (vEDS) is an uncommon genetic disorders characterized by arterial aneurysm, dissection and rupture, bowel rupture, and rupture of the gravid uterus. The frequency is estimated as 1/50, 000–1/200, 000 and results from pathogenic variants in COL3A1, which encodes the chains of type III procollagen, a major protein in vessel walls and hollow organs. Initial diagnosis depends on the recognitions of clinical features, including family history. Management is complex and requires multiple specialists who can respond to and manage the major complications. A summary of recommendations for management include: Identify causative variants in COL3A1 prior to application of diagnosis, modulate life style to minimize injury, risk of vessel/organ rupture, identify and create care team, provide individual plans for emergency care ("vascular EDS passport") with diagnosis and management plan for use when traveling, centralize management at centers of excellence (experience) when feasible, maintain blood pressure in the normal range and treat hypertension aggressively, surveillance of vascular tree by doppler ultrasound, CTA (low radiation alternatives) or MRA if feasible on an annual basis. These recommendations represent a consensus of an international group of specialists with a broad aggregate experience in the care of individuals with vascular EDS that will need to be assessed on a regular basis as new information develops. © 2017 Wiley Periodicals, Inc.